IMPACT OF AGRO AND AGROTECHNOLOGICAL FACTORS ON COTTON PRODUCTIVITY - Ubaydullayeva Shohista Hidoyatillo qizi (Scholar Express Journal, 2024)
In the field experiment, three different thicknesses of cotton bushes (80; 100 and 120 thousand per hectare, as well as 7.2; 9.0 and 10.8 plants per 1 pogonometer, respectively), two different irrigations relative to the limited field moisture capacity of the soil (ChDNS) regime (70-70-60 and 75-75-60%, as well as the irrigation regime 2-3-0 and 2-4-0, respectively) and the ratio of the two norms of fertilizer (NPK) (1: 0.7: 0, 5 and 1: 1: 0.5) were studied. The annual norm of fertilizers was: N200 P140 and K100 and N200 R200 and K100 kg. It was taken into account that the yield of cotton grown under conditions where the irrigation regime was 70-70-60% relative to the soil ChDNS (limited field moisture capacity) was higher in the years of experiments than the yield in the 75-75-60% regime irrigated variants. In the 70-70-60% irrigation regime, the average yield was 35.7-40.9 ts / ha, depending on the thickness of the bush and the ratio of fertilizers, while in the 75-75-60% irrigation regime the yield was 33.2-36.4 on average. ts / ha. The micronair index of fiber in cotton harvested from experimental variants was 4.3-4.5, and the micronair index of cotton fiber harvested from 70-70- 60% of irrigated variants was slightly higher than the 75-75-60% irrigation regime.
Keywords: Fertilization ratio; watering regime; bush thickness; fertility